Covariant M functions for higher spin - Scadron,MD; Jones,HF (Physical Review, 1968)
We give a systematic treatment of high-spin M functions in the Dirac-Rarita-Schwinger formalism. The main difficulty in writing such M functions is that apparently independent covariants are in fact related. We derive these relations (equivalence theorems) and show how they may be used to obtain a kinematic-singularity-free expansion of the M function. Many examples are given and the general pattern is discussed. We also analyze the restrictions due to discrete symmetries and show how to choose invariant amplitudes whose discontinuities are given by unitarity. The connection with the helicity formalism is stressed throughout. © 1968 The American Physical Society.